Molecular Motors Methods and Protocols - Sperry, Ann O.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2007)
Molecular motor proteins comprise three protein superfamilies: kinesins, dyneins and myosins. Together, these proteins produce force for movement in an incredibly wide variety of cellular processes including vesicular transport, cell division, nuclear migration, muscle contraction, mechanochemical transduction, among others. In addition, molecular motors are expressed in both simple eukaryotes and in a tissue specific manner in higher cells. This methods volume explores the extreme functional and structural diversity of molecular motors and presents methods relevant to each motor family. In addition, it describes techniques directed at motors that fall outside of the 3 characterized families (i.e. dynamin and F1ATPase). This volume of the Methods in Molecular Biology series is an essential reference for cell biologists examining the function of motor proteins in a range of model organisms using both in vitro and in vivo techniques. This volume is a valuble source for biochemists and molecular biologists as well.
Equilibrium Binding of Proteins to F-Actin -- Analysis of Calcium/Calmodulin Regulation of a Plant Kinesin Using Co-Sedimentation and ATPase Assays -- In Vitro and In Vivo Analysis of Microtubule-Destabilizing Kinesins -- Approaches to Kinesin-1 Phosphorylation -- Protein Modification to Probe Intradynein Interactions and In Vivo Redox State -- Methods to Study the Interactions of the Dynein Light Chains and Intermediate Chains -- Identification of Motor Protein Cargo by Yeast 2-Hybrid and Affinity Approaches -- In Situ Binding Assay to Detect Myosin-1c Interactions with Hair-Cell Proteins -- Ultrastructural Analysis of Kinesin-Related Motor Proteins During Spermatogenesis -- In Vitro Motility System to Study the Role of Motor Proteins in Receptor-Ligand Sorting -- Enrichment and Disassembly of Ectoplasmic Specializations in the Rat Testis -- Single-Molecule Observation of Rotation of F1-ATPase Through Microbeads -- The Use of FRET in the Analysis of Motor Protein Structure -- Structure Determination of the Motor Domain of Yeast Kinesin Kar3 by X-Ray Crystallography -- High-Resolution Structural Analysis of the Kinesin-Microtubule Complex by Electron Cryo-Microscopy -- Chemical-Genetic Inhibition of Sensitized Mutant Unconventional Myosins.
Keywords: Life sciences; Biochemistry; Proteins; Cell physiology; Life Sciences; Biochemistry, general; Protein Science; Cell Physiology; Electronic books